Spark plasma sintering of Sm2O3-doped aluminum nitride - Khor, Khiam Aik (2012)
The high sintering temperature required for aluminum nitride (AlN) at typically 1800 °C, is an impediment to its development as an engineering material. Spark plasma sintering (SPS) of AlN is carried out with samarium oxide (Sm2O3) as sintering additive at a sintering temperature as low as 1500–1600 °C. The effect of sintering temperature and SPS cycle on the microstructure and performance of AlN is studied. There appears to be a direct correlation between SPS temperature and number of repeated SPS sintering cycle per sample with the density of the final sintered sample. The addition of Sm2O3 as a sintering aid (1 and 3 wt.%) improves the properties and density of AlN noticeably. Thermal conductivity of AlN samples improves with increase in number of SPS cycle (maximum of 2) and sintering temperature (up to 1600 °C). Thermal conductivity is found to be greatly improved with the presence of Sm2O3 as sintering additive, with a thermal conductivity value about 118 W m−1 K−1) for the 3 wt.% Sm2O3-doped AlN sample SPS at 1500 °C for 3 min. Dielectric constant of the sintered AlN samples is dependent on the relative density of the samples. The number of repeated SPS cycle and sintering aid do not, however, cause significant elevation of the dielectric constant of the final sintered samples. Microstructures of the AlN samples show that, densification of AlN sample is effectively enhanced through increase in the operating SPS temperature and the employment of multiple SPS cycles. Addition of Sm2O3 greatly improves the densification of AlN sample while maintaining a fine grain structure. The Sm2O3 dopant modifies the microstructures to decidedly faceted AlN grains, resulting in the flattening of AlN–AlN grain contacts.